Pertimbangan Hakim Pengadilan Agama terhadap Perceraian Akibat Judi Online: Studi terhadap Dinamika Pembaharuan Hukum Islam di Indonesia - Maruba Rambe (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The development of digital technology has given rise to various new forms of social deviance, one of which is online gambling, which has a serious impact on family stability. This phenomenon has led to an increase in divorce cases in Religious Courts, with disputes and arguments influenced by online gambling addiction cited as the grounds for divorce. This study aims to analyze the considerations of Religious Court judges in adjudicating divorce cases resulting from online gambling and to examine its relevance to the dynamics of Islamic legal reform in Indonesia. This study employs a normative legal methodology using a statutory approach, a case-based approach, and a conceptual approach. Data sources were obtained from Religious Court rulings, the Compilation of Islamic Law, the Marriage Law, and contemporary Islamic legal literature. The results of the study indicate that Religious Court judges classify online gambling as a form of harm to the household that results in the loss of financial responsibility, economic instability, and psychological damage to the family. Although online gambling is not explicitly regulated in the Compilation of Islamic Law, judges adopt a progressive approach by interpreting it as a form of continuous conflict and quarrel. These considerations reflect the dynamics of Islamic legal reform, which adapts to developments in modern digital society.